Case report: Successful anterior temporal lobectomy in drug-resistant temporal lobe epilepsy associated with Sotos syndrome - Favi Bocca, Leonardo; Pereira Rodrigues, Thiago; Bortholin, Thiago; Targas Yacubian, Elza Márcia; Carrete Júnior, Henrique; Guaranha, Mirian; Silva Centeno, Ricardo (Frontiers in Neurology, 2023)
The Sotos syndrome is an autosomal dominant disorder characterized by haploinsufficiency of NSD1 gene, with some individuals affected by epilepsy and, rarely, drug-resistant seizures. A 47-years-old female patient with Sotos syndrome was diagnosed with focal-onset seizures in left temporal lobe, left-side hippocampal atrophy, and neuropsychological testing with decreased performance in several cognitive domains. Patient was treated with left-side temporal lobe resection and developed complete awake seizure control in 3-years of follow-up, with marked improvement in quality-of-life. In selected, clinically concordant patients, resective surgeries may play a significant role in improving patient's quality of life and seizure control.